Harnessing Technology for Research During the COVID-19 Pandemic: A Mixed Methods Diary Study Protocol. (17th March 2021) - Saltzman, L. Y.; Terzis, L. D.; Hansel, T. C.; Blakey, J. M.; Logan, D.; Bordnick, P. S.
Project Title: Psychosocial Reactions to a Global Pandemic: A Diary Study During COVID-19. Design: The study uses a mixed methods design that includes both a cross-sectional quantitative survey and qualitative diary entries submitted online eight times by student participants. Context of Study: The study timeline spans the full shutdown, phase 1 reopening, and phase 2 reopening of New Orleans Louisiana. Objectives: The study has three primary objectives: (1) To better understand the experiences of Social Work Students during the COVID-19 pandemic; (2) To explore risk and protective factors that influences Social Work Students' ability to cope with stressors and changes associated with the COVID-19 pandemic; and (3) to track changes over time in coping among Social Work Students during the COVID-19 pandemic. Study Population: Current Master of Social Work (MSW) Students enrolled at Tulane University during the COVID-19 Pandemic will be invited to participate in this study.